Knowledge and occupational practices of beauticians and barbers in the transmission of viral hepatitis: A mixed-methods study in Volta Region of Ghana - Silas Adjei-Gyamfi; Abigail Asirifi; Clotilda Asobuno; Felix Kwame Korang (PLoS ONE, 2025)
Background Hepatitis B and C viral (HBV and HCV) infections are endemic in Ghana. Also, the National Policy on Viral Hepatitis stipulates that there is unreliable data, limited knowledge, and a deficiency in research on viral hepatitis, especially among some high-risk workers in the eastern part of the country. This study therefore assessed the knowledge level and occupational practices of street beauticians and barbers in the transmission of HBV and HCV in the Volta Region of Ghana. Methods A cross-sectional mixed methods study was conducted in Volta Ghana from April to June 2021. An in-depth interview was used to collect data from five environmental health officers who were selected as key informants in the qualitative stage. Structured questionnaires/checklists and direct observations were employed to collect data from 340 street beauticians and barbers in the quantitative stage. During the qualitative stage, the process of coding, and mind mapping via thematic analysis was carried out. Furthermore, descriptive and inferential analyses were performed using Stata version 17.0 at a 95% significance level in the quantitative stage. Results Most street beauticians and barbers reported poor knowledge levels about HBV and HCV (67.0%), although the awareness of this viral hepatitis was high (88.2%). While almost one-third of the participants observed safe occupational practices (31.5%), about 29.0%, 49.4%, and 55.3% of them also followed hand hygiene protocols, wore protective clothes/gloves, and sterilized or disinfected tools after use respectively. Street beauticians and barbers with higher (tertiary) education (AOR = 6.15; 95%CI = 1.26–29.9; p = 0.024), those who had heavy workload of more than 20 customers per day (AOR = 3.93; 95%CI = 1.26–12.3; p = 0.019), and those who had work experience of at least four years (AOR = 1.65; 95%CI = 1.02–2.69; p = 0.040) were more likely to have good knowledge level about viral hepatitis. Additionally, beauticians were more likely to adhere to safe occupational practices as compared to barbers (AOR = 11.2; 95%CI = 3.46–36.3; p<0.001). The key informant interviews revealed that there was a lack of licensing, monitoring, and planned training for street beauticians and barbers, although their services are rampant in the Volta Region. Conclusion Participants showed high awareness but limited knowledge about HBV and HCV infections. The general safety practices among the participants were poor. Our study results suggest possible viral transmission through the activities of street beauticians and barbers which could be attributed to the lack of regulatory systems and training of these cosmetologists. Policy-makers and regulatory bodies should institute and enforce rigorous policies and guidelines on job-related safety measures and health practices including regular training, monitoring, screening, and vaccination programs for these high-risk community workers in Ghana.